2020
DOI: 10.3126/nmcj.v22i1-2.30023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of DIPSI and WHO 2018 criteria for diagnosis of GDM

Abstract: Gestational Diabetes Mellitus (GDM) is an important public health problem. Prevalence has shown an increasing trend and varies based on diagnostic criteria used and the ethnic group studied. It is more common in Asia. Presently, there is no international consensus on the screening and diagnostic criteria for GDM. The Diabetes in Pregnancy Study Group of India (DIPSI) guidelines recommend the non-fasting 75g oral glucose tolerance test (OGTT) as a single-step screening and diagnostic test for GDM, is simple, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A study by Shrestha B et al . [ 10 ] showed that the sensitivity of DIPSI was 73.68% and the specificity was 98.52%. The agreement between both the studies was 60–80%.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Shrestha B et al . [ 10 ] showed that the sensitivity of DIPSI was 73.68% and the specificity was 98.52%. The agreement between both the studies was 60–80%.…”
Section: Discussionmentioning
confidence: 99%
“…DIPI is a reliable, feasible and suitable method to diagnose GDM. The DIPSI criteria is just as sensitive as the WHO 2018 criteria in a hospital setting [22]. In a study conducted among 425 pregnant women, GDM was diagnosed in 5.88%, were to 80% among DIPSI and WHO 2018 criteria.…”
Section: Advantage Of Dipsi Criteria Over Other Methodsmentioning
confidence: 99%